Initiation of Gerai Tensi for screening and prevention of non-communicable diseases in the community - Susilawati, Tri Nugraha; Billah, Muhammad Muayyad; Syaputri, Dwi; Widyaningrum, Sherly Asri; Kusumastuti, Wijayanti; Buamona, Nur Sitra; Fahmi, Muhammad Izzul Widad; Rauf, Muhammad Abdul; Lutfinayati, Sofia; Cahyaningrum, Nabilla Fitria; Indallah, Nabila Wajihan; Puspitasari, Reni Nur (Journal of Community Empowerment for Health, 2024)
Background: The increased incidence of non-communicable diseases (NCDs) necessitates continuous promotional and preventive activities to reduce morbidity and mortality. Since NCDs cannot spread like infectious diseases, they are frequently neglected. In addition, NCDs represent a significant health burden as they can develop chronic consequences and lead to fatalities. The growing burden of NCDs is attributed to increased risk factors, including elevated blood pressure, obesity, body mass index, and blood sugar levels. Furthermore, NCDs can be the primary factor in long-term decreased productivity, leading to detrimental effects on social and economic resources. Some NCDs that are receiving the most attention and have the highest prevalence are hypertension and obesity. This paper aimed to present the prevalence of hypertension and obesity in a village community. Methods: We hosted a Gerai Tensi program as one of the community-based attempts to identify and screen for NCDs. This program was conducted in Dukuh Gowongan RT 003/ RW 002, Pucangan Village, Kartasura District, Sukoharjo Regency, Central Java Province, Indonesia. All the residents aged ≥15 years old were invited to attend Gerai Tensi. The participant's blood pressure, height, weight, and waist circumference were measured. Results: A total of 75 residents of Dukuh Gowongan attended Gerai Tensi. Most participants were female (53.3%), aged 46–55 (24.0%). There were 54.7% (41/75) of participants with hypertension, mainly classified as stage I hypertension (31/75; 41.3%), and 58.7% (44/75) of participants who were obese, mostly grade I obesity (28/75; 37.3%). Conclusion: Hypertension and obesity are prevalent in the community, reaching more than half of the study participants. Coordination with the community health centre and village representatives is required to optimize the promotion and prevention activities, the treatment of diseases, and the sustainability of the Gerai Tensi program.